Information Technology Integration Strategy in Public Library Services - Hazan Hazan; Zulkifli Ayub (Mahesa Research Center, 2024)
This study aims to identify the integration strategy of information technology in public library services in Bone Regency. Using a qualitative method with a case study approach, this research explores how information technology is applied in library management and its impact on service quality. A purposive sampling technique was used to select 15 informants consisting of 5 librarians, 5 library users, and 5 relevant stakeholders. The results show that the use of information technology, such as online catalogue systems and digital services, can improve the accessibility and efficiency of library services. Librarians in Bone Regency stated that technology helps them manage collections and serve users more quickly and accurately. Library users revealed that technology-based services make it easier for them to search for information and access reading materials remotely. However, some challenges, such as limited infrastructure and technical knowledge, still need to be overcome. This research highlights the importance of training and capacity building for librarians as well as increased investment in technology to maximise its benefits for public libraries in Bone Regency.